2021
DOI: 10.1021/acssensors.1c01437
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive and Reusable Graphene Oxide-Modified Double-Interdigitated Capacitive (DIDC) Sensing Chip for Detecting SARS-CoV-2

Abstract: This research reveals the promising functionalization of graphene oxide (GrO)-glazed double-interdigitated capacitive (DIDC) biosensing platform to detect severe acute respiratory syndrome coronavirus (SARS-CoV-2) spike (S1) proteins with enhanced selectivity and rapid response. The DIDC bioactive surface consisting of Pt/Ti featured SiO 2 substrate was fabricated using GrO/EDC-NHS/anti-SARS-CoV-2 antibodies (Abs) which is having layer-by-layer interface self-assembly chemistry method. This electroactive immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 41 publications
0
79
0
Order By: Relevance
“…Most importantly, it was found that this biochip exhibited selectivity against blood-borne antigens and can standby for almost ten days at 5 °C. Therefore, this biosensor can be considered portable, rapid point-of-care (POC) for early diagnosis of SARS-CoV-2 using real samples [ 52 ].
Fig.
…”
Section: Various Applications Of Graphene and Graphene-based Derivatives To Combat Sars-cov-2mentioning
confidence: 99%
“…Most importantly, it was found that this biochip exhibited selectivity against blood-borne antigens and can standby for almost ten days at 5 °C. Therefore, this biosensor can be considered portable, rapid point-of-care (POC) for early diagnosis of SARS-CoV-2 using real samples [ 52 ].
Fig.
…”
Section: Various Applications Of Graphene and Graphene-based Derivatives To Combat Sars-cov-2mentioning
confidence: 99%
“…As Lingervelder et al have reviewed, for general practitioners, the clinical utility of POC testing is the most critical aspect [ 65 ]. To ensure POCT’s usefulness to clinicians, future research [ 74 ], despite focusing on the analytical and technical performances of a test, should also tackle the aspects relating to the clinical utility and risks [ 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 ]. Moreover, in the case of smartphone-connected POCT devices, the issues related to data sensitivity, including privacy and protection against theft and medical advice, should be addressed [ 69 ].…”
Section: Challenges and Perspectives Towards Poc Diagnostics Of Damentioning
confidence: 99%
“…Biosensors 2021, 11, x FOR PEER REVIEW 10 of 14 risks[75][76][77][78][79][80][81][82][83]. Moreover, in the case of smartphone-connected POCT devices, the issues related to data sensitivity, including privacy and protection against theft and medical advice, should be addressed[69].…”
mentioning
confidence: 99%
“…Some of these methods based on viral gene detection ( Zhang et al, 2020 ) or viral protein detection ( Ahmadivand et al, 2021 ). Novel sensors based on the above two methods have been developed as well ( Kaushik, 2021 ; Mujawar et al, 2020 ; Sharma et al, 2021 ). These methods further enhance SARS-CoV-2 testing sensitivity, specificity or on-site detection availability.…”
Section: Introductionmentioning
confidence: 99%